Microbiota intestinal de pacientes com espondiloartrite axial: correlação com marcadores de permeabilidade intestinal, clínicos e dietéticos - Ana Carolina Garcia de Las Ballonas Campolina (2022)
Axial spondyloarthritis (SpA) are a group of chronic systemic inflammatory diseases primarily located in the axial skeleton - spine and sacroiliac joints. Studies have shown a strong genetic overlap between SpA and inflammatory bowel diseases indicating a relationship between events triggered in the gut and inflammation in the entheses and joints. Growing evidence also suggests that the gut microbiota is involved in the initiation and progression of axial SpA. Our objective in this study was to compare the microbiota of individuals with axial SpA compared to healthy controls and to analyze possible associations between the intestinal microbiota, intestinal permeability and clinical parameters of the disease. For this, 21 patients from the Hospital das Clínicas of the Federal University of Minas Gerais (HC-UFMG/EBSERH) and 21 healthy patients recruited through social networks were selected. Stool and blood samples were collected in addition to anthropometric and dietary data from all study participants. Our results showed that patients with axial SpA have serum markers of increased intestinal permeability, bacterial translocation, intestinal inflammation and increased levels of the inflammatory cytokine IL-17 compared to the healthy control group. In addition, these patients also had a higher percentage of body fat and a lower intake of folate and manganese. When evaluating the intestinal microbiota profile between the groups, we observed that axial spondyloarthritis was associated with changes in the abundance of 10 genera that were considered likely biomarkers in these patients with axial SpA. The most abundant genera were Acidaminococcus, Ruminococcus_gauvreauii_group, Howardella, Klebsiella, Methanobrevibacter, UBA1819 and Veillonella. At the same time, the genera Eubacterium_xylanophilum_group, Bilophila and Lachnoclostridium were significantly reduced in the axial SpA group compared to the control. We also observed significant correlations between some of these genera and between them and the metadata collected.